Analisis Karakteristik Lalu Lintas Data Internet Jaringan Seluler Aplikasi Web Video Streaming dan Video Conference - I Nyoman Wiranata; Renna Yanwastika Ariyana; Erna Kumalasari Nurnawati; Suparyanto Suparyanto (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
Internet service is an important thing during the Covid 19 Pandemic to do work from home, especially video conferencing and video streaming applications. This study aims to analyze the quality of internet network services on the Telkomsel cellular network internet network provider for video streaming and video conferencing web application services. Parameters measured on the quality of service are delay, jitter, packet loss. The method used in this research is to take  samples of video streaming and video conferencing applications for one week at different times and captured using the Wireshark application. Data collection was carried out in Mojayan, Klaten, Central Java. The results of this study showed video streaming and video conferencing applications have an average delay value of 37 ms in the "very good" category, jitter 223 ms in the "bad" category and 0% packetloss in the "very good" category. The results of this study indicate that the quality of web video streaming and video conferencing services from the Telkomsel provider at that location is running quite well according to the TIPHON standard. Service improvement needs to be done on the quality of loading so as to reduce buffering when the service is running